Checagem de conformidade arquitetural na modernização orientada a arquitetura - Chagas, Fernando Bezerra (2016)
Architecture-Driven Modernization (ADM) is a model-based initiative for standardizing reengineering processes. Its most important meta-model is KDM (Knowledge Discovery Metamodel), which is a platform and language-independent ISO standard. A important step in an Architecture-Driven Modernization is the Architectural Conformance Checking (ACC), whose goal is to identify the violations between the Planned (PA) and Current Architectures (CA) of a system. Although there are ACC approaches that act on source-code or proprietary models, there is none for hystems represented as KDM. This absence hinders the dissemination of ADM and increases the interest for research that investigates the suitability of KDM in this context. Therefore, in this paper, we present ArchKDM, a KDMbased ACC approach that relies exclusively on the KDM meta-model for representing i) the legacy system under analysis; ii) the PA; iii) the CA; and iv) the violations between them. ArchKDM is composed of three tool-supported steps: 1) Specifying the Planned Architecture; 2) Extracting the Current Architecture; and 3) Performing the Checking. Our goal is to investigate the suitability of KDM as the main representation in all ACC steps as well as to deliver an ACC approach in the ADM context. We evaluated steps 2 and 3 of the approach using two real-world systems and the results showed no false positives and negatives.